An efficient microwave-assisted hydrothermal synthesis of BaZrO3 microcrystals: growth mechanism and photoluminescence emissions - Macario, Leilane R. [UNESP]; Moreira, Mario L.; Andres, Juan; Longo, Elson [UNESP] (Royal Soc Chemistry, 2010)
The effect of different synthetic conditions (both template and chloride precursor concentration) on the morphologies of BaZrO3 microcrystals was systematically investigated. Three different templates, polyethylene glycol (PEG), cetyltrimethylammonium bromide (CTAB) and sodium dodecylsulfate (SDS), and two different chloride concentrations were used in the experiments. BaZrO3 microcrystals were obtained using the microwave assisted hydrothermal method (MWHT) at 140 degrees C for 40 min. BaZrO3 microstructures were characterized by powder X-ray diffraction (XRD), field-emission scanning electron microscopy (FE-SEM), Fourier transform Raman spectroscopy (FT-Raman) and photoluminescence (PL) measurements. The growth mechanism for the formation of BaZrO3 with decaoctahedron-shape was analyzed in detail, and we have found that the nature of the mechanism follows a non-classical growth process involving mesoscale self-assemblies of nanoparticles. Based on these findings, a relationship between the morphology and the photoluminescent behavior is proposed.